Emerging Public-Private Partnerships in Irrigation Development and Management - Darghouth, Salah (World Bank, Washington, DC, 2014)
The objective of this paper is to identify the possible role and opportunities for the private sector to participate with governments and farmers in developing and managing irrigation and drainage (I&D) infrastructure. Over the last 50 years, irrigated agriculture has been vital to meeting fast-rising food demand and has been key to poverty reduction. In the coming years the strong demographic demand for food is expected to continue, and intensified irrigated agriculture will have to provide close to 60 percent of the extra food. However, in recent years, the pace of irrigation expansion has been slowing, there has been less improvement in productivity, and water availability for irrigation is increasingly constrained. Governments have long led the expansion of large-scale irrigation, but performance has been suboptimal, and reforms that have been introduced have proved slow to improve efficiency and water service. Faced with this challenge, the I&D sector has been wrestling with three deep-seated problems: low water use efficiency, a high reliance on government financing, and poor standards of management and maintenance. Much of the search for improved investment and institutional models in I&D has been driven by the need to resolve these three problems. One solution that has been tested over the last two decades has been Participatory Irrigation Management (PIM) involving water user associations (WUAs) in the financing and management of schemes. This solution had its logical culmination in irrigation management transfer, the handover of responsibility for scheme operation and maintenance (O&M) to farmers and their organizations. This solution promised to relieve governments of both the fiscal burden and the responsibility for asset management and maintenance and to improve efficiency by empowering farmers. PIM has made impressive strides. However, efficiency has risen only marginally, and there are many schemes where O&M is beyond farmers' capacity.